Determinants of Target Victim Selection: A Case Study of Criminals from Gambaga Prisons - Azumah, Francess Dufie; Nachinaab, John Onzaberigu; Krampah, Samuel; Ayim, Pius Nzeh (Journal of victimology and victim justice (Print), 2020)
The study was conducted to explore the determinants of target victim selection by criminals, mode of operations adopted by criminals and the factors considered in the selection of victims by criminals. The study adopted a qualitative approach where simple random and purposively sampling techniques were used to select a sample size of 50 inmates in the Gambaga prisons. Interview guide was the main tool used for the data collection for this study. The study found that victimization influences criminal intentions and behaviour of an individual. The inmates noted that they like to attack victims in isolation and in dark places, especially at night. The study further found that criminals operated in gangs, in areas with darkness and in the night using caps and tattered dresses that anonymized them. They also used fear to traumatize their victims, monitor their victims, as well as operated with guns and knives and under special requests of other individuals in society.